Achieving Equity and Efficiency Simultaneously in the Primary Distribution Stage in the People's Republic of China - Lin, Justin Yifu; Liu, Peilin (2012)
This paper establishes a theoretical framework addressing the long-debated issue of efficiency and equity. Empirical evidence shows that a comparative-advantage-following development strategy promotes growth and narrows the income gap, achieving both efficiency in production and equity in income distribution. A review of the past three decades of reform reveals that development in line with the comparative advantage of the People's Republic of China accounts for its outstanding economic performance. The dominant causes of the country's current problems are the remaining distortions in prices and government interventions in resource allocation. Therefore, to put the government's "scientific development outlook" into practice and to realize development with quality and speed, the country should deepen marketoriented transformation by eliminating these distortions and interventions. The inclusiveness of development can be further strengthened with financially sustainable social security and transfer payment policies.